Allergy screening using a microcomputer. Issue 6340 (14th August 1982) - Pantin, C F; Merrett, T G
Abstract : Data are presented to show that a microcomputer can be programmed to: (1) analyse a standard allergy questionnaire, (2) reliably predict the ranked order probabilities with which IgE antibody tests will produce positive results, (3) store the IgE test results, and (4) print a comprehensive report that summarises and integrates the clinical and laboratory data. Consequently, the practitioner who refers a blood sample and a questionnaire completed by the patient to a centre where both can be analysed will obtain enough practical information to decide whether to treat or refer that patient to a specialist. The microcomputer is therefore potentially of great value in any preliminary allergy investigation.